2022
DOI: 10.1007/s00415-022-11182-z
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET, cognitive functioning, and CSF biomarkers in patients with obstructive sleep apnoea before and after continuous positive airway pressure treatment

Abstract: Introduction Dysregulation of cerebral glucose consumption, alterations in cerebrospinal fluid (CSF) biomarkers, and cognitive impairment have been reported in patients with obstructive sleep apnoea (OSA). On these bases, OSA has been considered a risk factor for Alzheimer’s disease (AD). This study aimed to measure cognitive performance, CSF biomarkers, and cerebral glucose consumption in OSA patients and to evaluate the effects of continuous positive airway pressure (CPAP) treatment on these bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 64 publications
0
16
0
2
Order By: Relevance
“…Similar to the above-mentioned link between Alzheimer’s pathology and AH, there are also reports on associations of OSA with amyloid pathology 43 , 85 contributing to the understanding of the pathophysiological consequences of OSA linked to hypoxia-induced dysfunctions 86 . Another aspect in this context is sleep fragmentation as an OSA-related factor resulting into cognitive decline 21 .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Similar to the above-mentioned link between Alzheimer’s pathology and AH, there are also reports on associations of OSA with amyloid pathology 43 , 85 contributing to the understanding of the pathophysiological consequences of OSA linked to hypoxia-induced dysfunctions 86 . Another aspect in this context is sleep fragmentation as an OSA-related factor resulting into cognitive decline 21 .…”
Section: Discussionmentioning
confidence: 67%
“…Neuroimaging studies indicated not only functional brain alterations in OSA 39 but also recovery after CPAP-treatment in brain regions which were affected by hypoxic damage 40 i.e. the hippocampus 41 , 42 , the frontal gyri 43 , and the default mode network 44 , 45 .…”
Section: Introductionmentioning
confidence: 99%
“…The Aβ42 contributes to cerebral amyloid angiopathy in AD and decreased concentrations of Aβ42 in CSF have all proven to be useful in the diagnosis of AD ( McKhann et al, 2011 ). Currently, increasing studies have linked OSA to decreased concentrations of Aβ42 in CSF ( Ju et al, 2016 ; Liguori et al, 2017 , 2019 ; Sharma et al, 2018 ; Diáz-Román et al, 2021 ; Fernandes et al, 2022 ). However, there were also studies indicating no significant difference of Aβ42 levels in CSF of OSA patients ( Osorio et al, 2014 ; Diáz-Román et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of p-tau and t-tau in CSF could reflect cortical tangle formation and axonal degeneration or injury and can be used as a general marker in AD ( Kazim et al, 2022 ). Many studies have reported increased CSF t-tau and p-tau levels in OSA patients ( Diáz-Román et al, 2021 ; Fernandes et al, 2022 ). Nevertheless, several studies show no significant difference in CSF t-tau and p-tau levels in OSA patients ( Osorio et al, 2014 ; Ju et al, 2016 ; Liguori et al, 2017 , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation